Beyond Bach: Music and Everyday Life in the Eighteenth Century - Talle, Andrew (Urbana, IL University of Illinois Press, 2017)
Reverence for J. S. Bach's music and its towering presence in our cultural memory have long affected how people hear his works. In his own time, however, Bach stood as just another figure among a number of composers, many of them more popular with the music-loving public. Eschewing the great composer style of music history, Andrew Talle takes us on a journey that looks at how ordinary people made music in Bach's Germany. Talle focuses in particular on the culture of keyboard playing as lived in public and private. As he ranges through a wealth of documents, instruments, diaries, account ledgers, and works of art, Talle brings a fascinating cast of characters to life. These individuals--amateur and professional performers, patrons, instrument builders, and listeners--inhabited a lost world, and Talle's deft expertise teases out the diverse roles music played in their lives and in their relationships with one another. At the same time, his nuanced recreation of keyboard playing's social milieu illuminates the era's reception of Bach's immortal works.
Keywords: 18th Century (1701-1800); Music history; Cultural history; Germany